Evaluation of rheological properties of soft lining materials with different composition under various temperatures - Şule Nur Macit; Ayhan Gürbüz; Perihan Oyar (BMC, 2024)
Abstract Purpose The aim of this in vitro study was to evaluate the changes the rheological properties of some soft lining materials, to compare the rheological properties and viscoelastic behaviour at different temperatures. Materials and methods Five soft lining materials (acrylic and silicone based) were used. the storage modulus (G'), loss modulus (G"), tan delta (tan δ) and complex viscosity (η') were chosen and for each material, measurements were repeated at 23, 33 and 37  °C, using an oscillating rheometer. All data were statistically analyzed using the Mann Whitney U test, Kruskal Wallis test and Conover's Multiple Comparison test at the significance level of 0.05. Results Soft lining materials had different viscoelastic properties and most of the materials showed different rheological behavior at 23, 33 and 37  °C. At the end of the test (t¹5), at all the temperatures, Sofreliner Tough M had the highest storage modulus values while Visco Gel had the highest loss Tan delta values. Conclusions There were significant changes in the rheological parameters of all the materials. Also temperature affected the initial rheological properties, and polymerization reaction of all the materials, depending on temperature increase. Clinical implications Temperature affected the initial rheological properties, and polymerization reaction of soft denture liner materials, and clinical inferences should be drawn from such studies conducted. It can be recommended to utilize viscoelastic acrylic-based temporary soft lining materials with lower storage modulus, higher tan delta value, and high viscosity in situations where pain complaint persists and tissue stress is extremely significant, provided that they are replaced often.